Grit, discounting, & time inconsistency - König-Kersting, Christian; Trautmann, Stefan T. (Journal of risk and uncertainty, 2025)
We study the association of the perseverance of effort and the consistency of interests components of the psychological measure of grit with economic measures of impatience and time inconsistency in the general population. We find that impatience is associated with grit through the perseverance of effort component. No association of time inconsistency with grit is found. Predicting participants’ financial and health outcomes and behaviors, we find that impatience and grit are predictive for both outcomes, but this is not the case for time inconsistency. Our findings suggest that it can be beneficial for empirical studies of intertemporal decisions to include economic impatience and psychological grit measures.
Online veröffentlicht: 17. Juni 2025
Gesehen am 17.10.2025
Keywords: Aufsatz in Zeitschrift